Công nghệ mới trong xây dựng và sửa chữa đường băng sân bay - Hà, Huy Cương (2011)
Tác giả: Hà Huy Cương, GS, TS; Nguyễn Hữu Trí, PTS; Nguyễn Xuân Đào, PGS, PTS; Võ Văn Thảo, PGS, PTS; Phạm Hữu Phức, GS, PTS; Phạm Cao Thăng, PTS; ê Đức Tiến, PTS; Nguyễn Đức Khánh, KS -- Từ khóa: Đường băng; Sân bay; Hư hỏng; Xây dựng; Sửa chữa; Bê tông nhựa; Bê tông - xi măng; Bê tông asphalt; Nhựa đường